The benefit of hypothermia in experimental ischemic stroke is not affected by pethidine. Issue 3 (3rd July 2012) - Sena, Emily S.; Jeffreys, Amy L.; Cox, Susan F.; Sastra, Stephen A.; Churilov, Leonid; Rewell, Sarah; Batchelor, Peter E.; van der, H. Bart; Macleod, Malcolm R.; Howells, David W.
<x xml:space="preserve">Abstract</x> Background Hypothermia is a promising experimental treatment for acute ischemic stroke. Human trials are still at an early stage, with the focus now on using hypothermia in awake patients. Pethidine (meperidine) is the principle agent used to control shivering in humans; however, whether it has any modulating effects on the neuroprotective efficacy of hypothermia is unknown. Aim The aim of this study was to determine if pethidine influences the neuroprotective effect of hypothermia in experimental stroke. Methods Seventy‐two male spontaneously hypertensive rats were anesthetized with isoflurane and randomly assigned to either normothermia (37·4°C rectal temperature); hypothermia (33°C maintained for 130 mins); normothermia plus pethidine (2·5 mg/kg); or hypothermia plus pethidine. Temporary (90 mins) endovascular occlusion of the middle cerebral artery was induced blinded to treatment allocation and was confirmed with laser Doppler flowmetry. Pethidine and cooling were started immediately after vessel occlusion. Animals in the normothermia group had active temperature management using a heat lamp and fan. Assessments of outcome were carried out 24 after the induction of injury. Results Thirteen animals met our prespecified criteria for exclusion, and data for 59 rats were presented here. Hypothermia was associated with a 63% reduction in infarct size, and pethidine had no significant impact on the efficacy of hypothermia. No effects were observed in neurobehavioral outcome or edema volume across experimental groups. Conclusions The effects of hypothermia in a model of focal ischemia are not affected by administration of pethidine.